Control interno del Comercial Ferretería Arroba “Franquicia Disensa” de la parroquia La Unión del periodo 2021. - Vélez Frías, Krocnel Leonardo (2022)
In the following case study is focused on the internal control of the commercial hardware company Arroba "Franquicia Disensa" in which problems are presented which were taken to be able to raise the different objectives of which the main objective is to carry out an analysis to be able to identify the shortcomings in the different areas and carry out an adequate planning. The methods chosen to carry out the study within the company were inductive and descriptive method, since through the methods already mentioned we obtained a series of relevant information to carry out the realization of this study. The internal control designed and implemented was executed in a very orderly and uniform manner in accordance with the established rules and procedures, for the fulfillment of our objectives.